PENYEBARAN DAN KARAKTERISTIK SARANG BERBIAK KOMODO (Varanus komodoensis Ouwens, 1912) DI LOH LIANG PULAU KOMODO TAMAN NASIONAL KOMODO NUSA TENGGARA TIMUR - M Muslich; Agus Priyono (Department of Forest Resources Conservation and Ecotourism - IPB University, 2005)
The study on distribution and characteristic of the nest of komodo was conducted during March and April 2004 in Komodo National Park. Based on the field observation in Loh Liang resort indicated that the distribution of the nest of komodo were mainly on the flat areas (